2018
DOI: 10.1007/s00414-018-1781-0
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological analysis of the variability of the human skeleton: forensic implications

Abstract: One of the fundamental questions in forensic medicine and anthropology is whether or not a bone or bone fragment is human. Surprisingly at times for the extreme degradation of the bone (charred, old), DNA cannot be successfully performed and one must turn to other methods. Histological analysis at times can be proposed. However, the variability of a single human skeleton has never been tested. Forty-nine thin sections of long, flat, irregular and short bones were obtained from a well-preserved medieval adult h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…More recent tissues (osteonal and fibrous tissue) are less mineralized and more immature, leading to differences in heat‐induced particle growth. Furthermore, considerable intrabone variability in histological tissue has been reported thus demonstrating that bones are quite heterogeneous (Cummaudo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…More recent tissues (osteonal and fibrous tissue) are less mineralized and more immature, leading to differences in heat‐induced particle growth. Furthermore, considerable intrabone variability in histological tissue has been reported thus demonstrating that bones are quite heterogeneous (Cummaudo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Variability of histological structures occurs in different locations within the same transverse section . These spatial changes around the bone cortex were most likely due to differences in biomechanical loading .…”
Section: Resultsmentioning
confidence: 99%
“…Validation studies have demonstrated that erroneous analysis and interpretation of histological variables and sampling strategies, often due to limited methodological instruction, may be a contributing factor to the infrequent application of histological age estimation methods, thereby limiting refinement and replicability studies. Rarely is the entire transverse section sampled , but use of a smaller ROI may not capture the histomorphometric variance present in a bone sample . Methods that evaluate the rib, which presents a reduced cortical area, often assess 50% of the cortex using a checkerboard pattern , despite the methods being most accurate when the entire cortex is evaluated .…”
mentioning
confidence: 99%
“…Factors other than the number of osteons may affect the representativeness. In two studies, Cummaudo and colleagues [61,62] reported the presence of both histomorphological and histomorphometric variability between different bones of the same individual, in different portions of the same bone, and in different parts of the same section. This variability may affect the effectiveness of histomorphometric methods and lead to wrong conclusions, especially for fragmented specimens [62].…”
Section: Observability and Histomorphometry Variabilitymentioning
confidence: 99%